Fighting Stereotypes and Discrimination: Promoting Inclusion for Individuals with Albinism - Lasaiba, Irvan; Lasaiba, Djamila (GEOFORUM, 2023)
Albinism is a genetic condition characterized by inadequate production of melanin in the body, resulting in changes in skin, hair, and eye color. Individuals with albinism often face challenges in daily life and frequently experience discrimination and prejudice from society. This paper uses a literature-based method, exploring various relevant sources to examine the background of albinism and the associated social phenomena. It also discusses the types of albinism, the causes and genetic factors involved, and the social and psychological impacts of stereotypes and prejudice. The paper further explores the challenges faced by individuals with albinism, including discrimination in education, healthcare, employment, and daily life. Addressing this issue is crucial to combating existing stereotypes and prejudice while promoting social inclusion. Support, education, and broader public awareness are necessary to create an inclusive environment and reduce discrimination against individuals with albinism. Through collaborative efforts from the government, educational institutions, society, and individuals, we can make a more just and inclusive society for individuals with albinism, where they can live with dignity and have equal opportunities.